Effect of electric induced triploidization on sex ratio, growth and gonad histology of red hybrid tilapia - V. T. Okomoda (2020)
© 2020 Elsevier B.V. Some effects of electric induced triploidization on Red Hybrid Tilapia were investigated in this study. With the aid of 12 V battery, electric current was used to induce shock in fertilized eggs of red hybrid tilapia for a duration of 10 min (at about 4 min after fertilization). Triploidy was confirmed to be 93 ± 1.6% using the exclusive triploid range of cell major axis previously reported for the same species and cytogenetic analysis (3n = 66 and 2n = 44). After four months of culture, it was observed that triploid induced progenies were male biased (%male = 77 ± 1.2%) compared to their diploid counterparts (%male = 46 ± 0.8%). The triploid female progenies observed in this study also showed significantly low values of gonadosomatic index which were thought to have been a result of the underdevelopment of the ovaries as revealed by gonad histology. Also, the final weight of the male triploid progenies was significantly higher compared to those of the diploids. It was concluded that the induction of triploidy in Red Hybrid Tilapia through electric shock among other things may have skewed sex ratio in favour of the males.